Cognitive Correlates of Reading Fluency in Chinese School-Aged Children - Bai, Jing; Li, Wenlong; Yang, Yang; Wu, Jianhui; He, Wei; Xu, Min (Frontiers in Psychology, 2020)
Previous studies have showed that reading fluency is strongly associated with cognitive skills including rapid automatized naming, phonological awareness, orthographical awareness and so on. However, these studies are largely based on alphabetic languages, and it remains unclear as to what cognitive factors contributed to the development of reading fluency in logographic Chinese, a language in which the graphic forms map onto morphemes (meaning) rather than phonemes. In Study 1, we tested 179 Chinese children aged 6 to 9 on a set of cognitive tasks as well as word reading accuracy and sentence reading fluency. Results showed that rapid naming, writing fluency and phonological awareness significantly predicted reading fluency in both beginning and intermediate readers. In addition, while the contribution of rapid naming and writing fluency increased with grades, the effect of phonological awareness decreased. In Study 2, we examined the role of visual crowding in reading fluency in a subgroup of 86 children and found that visual crowding accounted for unique variance of individual differences in reading fluency. The findings reflect both universal and language-specific cognitive correlates of reading fluency, and provide important implications for potentially effective treatment for individuals who suffered from Chinese reading disabilities, particularly in terms of reading fluency.